Aquaculture and Fisheries Science Sustainable Practices in Marine and Freshwater Systems - Choudhury, Mumina Islam; Sumidha , E.; Singh , Priyank Kumar; Ramesh, T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This article delves into the evolving realm of Aquaculture and Fisheries Science, with a focus on sustainable practices in both marine and freshwater systems. It presents a comprehensive overview of the current state of these industries, including their global impact, economic significance, and the crucial role they play in ensuring food security. The challenges faced by these sectors, particularly in the context of sustainability, are thoroughly examined. These challenges encompass overfishing, environmental degradation, and the effects of climate change on aquatic ecosystems. The article highlights innovative and eco-friendly practices being adopted in aquaculture, such as integrated multi-trophic aquaculture, advancements in breeding, and efficient feed management. In the realm of fisheries, it discusses the implementation of effective management strategies like quota systems and the establishment of marine protected areas. The role of modern technology in enhancing sustainability is also explored, showcasing the potential of AI, satellite monitoring, and advanced tracking systems in improving fish population management and ecosystem conservation. Furthermore, the socio-economic dimensions of sustainable aquaculture and fisheries are analyzed, emphasizing the importance of policy, governance, and community involvement.